Perancangan Interior Hotel Resort Pines Garden di Tretes, Pasuruan, Jawa Timur - Yussy Riadi (Intra, 2015)
Resort is a hotel which is usually located outside the city , in the mountains , on the beach , at the edge of the lake or in the area where the vacation / recreation which provide facility to people who are on vacation in a relatively long period of time . Hotel Resort Pines Garden is a three-star hotel with 31 guest rooms that are close to the waterfall tourist rides Kakek Bodo . Interior design hotel resort Pines Garden aims to improve the image and quality of the hotel so as to increase the number of visitors (commercial). particularly attract the tourists who visit Tretes tourist areas , or for those who simply want a vacation / recreation. The design concept of